Anticoagulant effects, substance basis, and quality assessment approach of Aspongopus chinensis Dallas - Jinzhou Fu; Guoli Zhang; Hongbing Peng; Zijie Xu; Yimei Liu; Keli Chen; Juan Li (PLoS ONE, 2025)
Background Aspongopus chinensis Dallas holds both medicinal and culinary significance in China. Notably, in regions such as Guizhou and Yunnan, it has been traditionally used as an ethnic remedy for treating various conditions, including stomach coldness, pain, kidney deficiencies, and impotence, among other ailments. This study aims to explore the chemical constituents and anticoagulant activity of A. chinensis. Methods Ultraperformance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was employed for the UPLC fingerprint analysis. The isolated compounds underwent in vitro assays to their evaluate anticoagulant properties and effects on protein fibril activity. Network pharmacology was utilized to predict potential anticoagulant targets. Furthermore, animal experiments were conducted to measur coagulation factors and assess the in vivo anticoagulant activity. Results Our findings indicate that 10 compounds were identified through UPLC-Q-TOF-MS analysis, with four compounds (uracil; 6-hydroxyquinolinic acid; 1,4-dihydro-4-oxoquinoline-2-carboxylic acid; delicatuline B) were isolated and identified from the n-butanol extract of A. chinensis. Furthermore, principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (PLS-DA) of the UPLC fingerprint data revealed significant differences between A. chinensis and its similar insects. Notably, 1,4-dihydro-4-oxoquinoline-2-carboxylic acid has been identified as a potential standard reference substance for content determination. The isolated compounds showed anticoagulant properties, and the mRNA expression levels of MMP9 and PTGS2 were significantly reduced in LPS-induced RAW264.7 cells, further supporting the network pharmacology analysis. Animal experiments confirmed the potent anticoagulant effects of A. chinensis, likely associated with the intrinsic coagulation pathway and the inhibition of platelet aggregation, Conclusion This research provides a quality assessment method for A. chinensis, and has also demonstrated its anticoagulant functions and substance basis